Parasite infections, neuroinflammation, and potential contributions of gut microbiota - Alloo, Jérémy; Leleu, Ines; Grangette, Corinne; Pied, Sylviane (Frontiers in Immunology, 2022)
Many parasitic diseases (including cerebral malaria, human African trypanosomiasis, cerebral toxoplasmosis, neurocysticercosis and neuroschistosomiasis) feature acute or chronic brain inflammation processes, which are often associated with deregulation of glial cell activity and disruption of the brain blood barrier’s intactness. The inflammatory responses of astrocytes and microglia during parasite infection are strongly influenced by a variety of environmental factors. Although it has recently been shown that the gut microbiota influences the physiology and immunomodulation of the central nervous system in neurodegenerative diseases like Alzheimer’s disease and Parkinson’s , the putative link in parasite-induced neuroinflammatory diseases has not been well characterized. Likewise, the central nervous system can influence the gut microbiota. In parasite infections, the gut microbiota is strongly perturbed and might influence the severity of the central nervous system inflammation response through changes in the production of bacterial metabolites. Here, we review the roles of astrocytes and microglial cells in the neuropathophysiological processes induced by parasite infections and their possible regulation by the gut microbiota. Graphical abstract: The three-way dialogue between parasites, the gut microbiota, and glial cells.